The Effect of Client Progress Feedback on Child/Adolescent's Group-Counseling Outcomes. Issue 4 (1st October 2016) - Shechtman, Zipora; Sarig, Or
Abstract : Client progress feedback provided to therapists has become a viable method to improve outcomes of individual therapy for adults. Little is known of the impact of progress feedback in group treatment and for children and adolescents in group. Using a randomized control study of 220 children and adolescents with behavior problems, this research investigated the feedback system in child and adolescent group counseling. The Youth Outcome Questionnaire (Y-OQ-30) was employed to monitor clients' symptom reduction. In addition, bonding with the counselor and the group were measured. Results indicated progress for all participants, but feedback provision made no impact. Similarly, no impact of feedback provision was found on bonding with the therapist and the group. Results are discussed in regard to the type of population involved and group modality.